2001
DOI: 10.1509/jmkr.38.2.143.18840
|View full text |Cite
|
Sign up to set email alerts
|

Response Styles in Marketing Research: A Cross-National Investigation

Abstract: Response styles are a source of contamination in questionnaire ratings, and therefore they threaten the validity of conclusions drawn from marketing research data. In this article, the authors examine five forms of stylistic responding (acquiescence and disacquiescence response styles, extreme response style/response range, midpoint responding, and noncontingent responding) and discuss their biasing effects on scale scores and correlations between scales. Using data from large, representative samples of consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
897
0
28

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 973 publications
(986 citation statements)
references
References 42 publications
13
897
0
28
Order By: Relevance
“…If these strategies are insufficient to prevent acquiescence, post hoc controls should be built into the questionnaire. For example, balanced scales consisting of an equal number of regular and reversed items should be used, or unrelated items should be included that enable the formation of an explicit measure of acquiescence (Baumgartner & Steenkamp, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…If these strategies are insufficient to prevent acquiescence, post hoc controls should be built into the questionnaire. For example, balanced scales consisting of an equal number of regular and reversed items should be used, or unrelated items should be included that enable the formation of an explicit measure of acquiescence (Baumgartner & Steenkamp, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…In particular, a) we ensured that only Russian tourists participated to reduce the coverage error (Moutinho & Chien, 2007), b) we reflect the perceptions of 14.2% of Russian tourists that visited Greece in 2014(HCAA, 2014 to avoid sampling error (Zikmund & Babin, 2007), c) we achieved an 83.86% response rate, which suggests that nonresponse error is not an issue (Baumgartner and Steenkamp, 2001), and d) we added an "0 = I don't know/I cannot reply" option to the 7-point Likert scale to reduce measurement error (Weijters, Cabooter, & Schillewaert, 2010).…”
Section: Sampling Procedures and Data Collectionmentioning
confidence: 99%
“…A three-process response model. Past work on response style (Baumgartner & Steenkamp, 2001;Cronbach, 1950;Rorer, 1965;Paulhus, 1991) showed that a respondent's use of a rating scale can be determined by variables that are unrelated to the attitude being measured. For example, some respondents may avoid using extreme response categories even if they feel strongly about a topic.…”
Section: Involvement Direction and Intensity In Likert Scalesmentioning
confidence: 99%